Pemberdayaan Masyarakat Melalui Pendidikan Perencanaan dan Pengelolaan Keuangan Rumah Tangga dan Investasi bagi Ibu Rumah Tangga dalam Rangka Peningkatan Kualitas Hidup Keluarga - Buchdadi, Agung Dharmawan; Solikha , Solikha; A. W. S Waspodo, Agung; Kurnianti, Destria (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
The aim of this study is to improve knowledge and skill about financial literacy, especially for woman who take the most responsibilities to manage finance in her household. Attended by 13 housewives, the method used in this activity is; first, explanation using power point slides and LCD projector; second, experience sharing and discussion; distributing quetionaire to measure their level of financial literacy, discussed about their characteristics on investment and what kind of product which is suit to their ability to accept risk. Held on May 7, 2017, the community service is funded by DIPA BLU Faculty of Economics, Universitas Negeri Jakarta. The result shows that only few participants understand how to measure their financial health and what kind of investment products that suit to their characteristics as an investor.